Medicinal and culinary importance of edible flowers of indian origin: an in-depth review - Aditi Gupta; Shivangi Sharma; Devyani Rajput; Umesh K. Patil (Discover Food)
Abstract This comprehensive examination delves into the multifaceted characteristics of edible flowers, underlining their significance as sources of natural ingredients and their medicinal properties. The review commences with an introductory section emphasizing edible flowers' cultural and health importance. It proceeds to explore the botanical diversity of edible flowers, encompassing their geographical distribution. Emphasis is placed on the bioactive constituents of these flowers, with a focus on their potential health benefits and various molecular targets for the treatment of several chronic disorders. Culinary and medicinal uses are examined, illustrating their adaptability across diverse cultural contexts. Their nutritional richness is highlighted through comparative analysis. Safety considerations and regulatory frameworks ensure consumer protection. Future prospects underscore innovation, discussing potential applications in the food industry and avenues for further research. The analysis concludes by summarizing key findings and discussing future implications, highlighting the intriguing potential of edible flowers as natural components for various applications in food, health, and beyond. Graphical abstract